A Comprehensive Review of Anesthesia and Pulmonary Hypertension: Insights into Preoperative Preparation, Monitoring and Treatment - Çekmen, Nedim; Gökdemir, Begüm Nemika (Medicine and Medical Research: New Perspectives Vol. 11, 2024)
Pulmonary hypertension (PH) is a complex disease of the cardiopulmonary system. The most common causes of postoperative mortality in PH patients are acute RVF, arrhythmias (particularly atrial fibrillation [AF]), ischemia, congestive heart failure (CHF), unstable hemodynamic status, hypoxia, respiratory and renal failure, sepsis, and stroke. Perioperative management of PH is one of the most challenging issues for anesthetists. Morbidity and mortality are significantly high in PH patients undergoing surgery due to right heart failure, arrhythmia, atrial fibrillation, ischemia, hemodynamic instability, hypoxia, respiratory failure, renal failure, sepsis, and stroke. Detailed preoperative evaluation and correct anesthetic management will significantly increase the chances of a successful peri-operative outcome in these patients. In PH patients, it is important that more than one physician, including anesthesiologist, intensivist, pulmonologist, cardiologist, and surgeon, discuss the patient’s possible difficulties and complications with a multidisciplinary approach and make a decision. In order to optimize the management of PH patients, it is necessary to comprehensively evaluate the underlying cause, pathophysiology, risk factors, course, and treatment of the disease. Currently, no evidence-based information is available for choosing general, regional, or combined anesthesia as anesthetic techniques for PH patients. A balanced anesthesia technique, including inhalation or intravenous agents, appropriate regional anesthesia (RA), opioids, and \(α\)-2-adrenoceptor agonists may provide the most uniform hemodynamic profile in these patients. The basis of anesthesia management should be to prevent and treat triggering factors, provide perfusion pressures, and optimize right ventricular functions. Advanced monitoring, pulmonary vasodilator therapies, adequate anesthesia and analgesia, and appropriate ventilator settings should be performed for patients with PH. Patients with PH should be followed in the intensive care unit in the first 48–72 h postoperatively. In PH patients, advanced intraoperative and postoperative follow-up, pulmonary vasodilator treatments, adequate anesthesia, and analgesia should be considered. It is essential to optimize the patient for surgery in a nonemergency situation and to organize treatment and education of the patient for the long-term period of the disease. This book chapter aims to focus on appropriate preoperative preparation, perioperative monitoring, anesthesia and ventilator management, pain control, preventive methods, and treatment in patients with PH in light of the literature.